A formação continuada de professoras e suas relações com a prática docente - Geralda Aparecida de Carvalho Pena (1999)
This dissertation is intended to find out how teachers of initial series of fundamental education analyze their own process of continued education along their careers and the relationship between this education and their teaching practices. The field research was carried out with eight teachers at different stages of their careers, and working in three urban schools from the Municipal Education System in Ouro Preto, Minas Gerais, Brazil. The study was based upon interviews with the teachers, and principals and supervisors from the schools where they work, representatives from the Municipal School Authority and the Regional Superintendency of Education from Ouro Preto, as well as document analysis. Assuming that continued education is a complex process comprising different moments in which the teachers construct knowledge about their own work, my attempt was to develop an analysis considering formal activities (courses and pedagogical workshops), the school as a locus of education and the teaching practice itself. I tried to analyze the teachers perception of the role of continued education in their careers, the prospects and limits of this education as well as the factors that triggered changes in teaching practices and the obstacles to bring about such changes. The analysis of the collected data revealed that teachers continued education is a complex process and that the main factors that trigger changes in teaching practices are related to challenges brought about by teaching and to the support given by the school to such changes. It also evidenced that teaching is limited by several factors related to the way the teachers work is seen in the wider context of school and education system. Finally, this study points out some challenges that must be faced in teachers continued education which include the organization of activities that can provide a revision of the educators role, the allowance of time exclusively for continued education activities during working hours, the need of specific projects in the schools in order to guarantee a well-based reflection on teaching practices and the revision of the Education Authorities role in the implementation of teachers continued education policies